Poly(ϵ-Caprolactone)-Methoxypolyethylene Glycol (PCL-MPEG)-Based Micelles for Drug-Delivery: The Effect of PCL Chain Length on Blood Components, Phagocytosis, and Biodistribution - Hou Z; Zhou W; Guo X; Zhong R; Wang A; Li J; Cen Y; You C; Tan H; Tian M (International Journal of Nanomedicine, 2022)
Zemin Hou,1,2,* Wencheng Zhou,1,2,* Xi Guo,2 Rui Zhong,3 Ao Wang,4 Jiehua Li,4 Ying Cen,1 Chao You,2 Hong Tan,4 Meng Tian2 1Department of Burn and Plastic Surgery, National Clinical Research Center for Geriatrics, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Department of Neurosurgery and Neurosurgery Research Laboratory, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 3Institute of Blood Transfusion, Chinese Academy of Medical Science & Peking Union Medical College, Chengdu, Sichuan, People’s Republic of China; 4College of Polymer Science and Engineering, State Key Laboratory of Polymer Materials Engineering, Sichuan University, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Meng Tian, Department of Neurosurgery and Neurosurgery Research Laboratory, West China Hospital, Sichuan University, No. 37 Guoxue Alley, Wuhou District, Chengdu, Sichuan Province, 610041, People’s Republic of China, Tel +86 28 85164168, Email tianmeng@scu.edu.cnBackground: The main challenge of polymeric micelles as drug delivery systems is that the actual delivery efficiency is not as high as expected, which is closely related with the interactions with the complex biological environments such as blood components, phagocytosis, and biodistribution. Herein, we expect to understand these concerns for the clinically relevant micelles that composed of methoxypolyethylene glycol (MPEG) with identical chain length And poly(ϵ-caprolactone) (PCL) with tunable chain length (PCLn-MPEG) (n=20, 30, and 40) wherein doxorubicin was encapsulated as a model drug.Methods: The doxorubicin-loaded PCLn-MPEG micelles were prepared by a dialysis method and characterized by dynamic light scattering and transmission electron microscopy. The surface PEG density and chain conformation were investigated by dissipative particle dynamics simulation. The stability of the micelles was detected by nanoparticle tracking analysis. The effects of PCL chain length on the blood components, phagocytosis, and biodistribution were assayed in vitro and in vivo.Results: The micelles exhibited spherical morphology with a diameter about 30nm. The PEG chain conformation from “mushroom-like” to “brush-like” was evident. The micelles have no remarkable effect on the red blood cells, blood coagulation, and platelet activation. Interestingly, the protein adsorption was affected and dependent on the chain conformation, with lowest adsorption for PCL30-MPEG, which also has the loWest phagocytosis. The stability of the micelles was in the order of PCL40-MPEG>PCL30-MPEG>PCL20-MPEG which was dependent on the PCL chain length. The micelles mainly accumulated in liver, with the order consistent with their stability, indicating that, besides the phagocytosis, the stability of the micelle plays an important role in biodistribution as well. The related mechanisms were proposed and discussed.Conclusion: Manipulating the PEG/PCL ratio of the micelle is an effective approach to modulate the protein adsorption, phagocytosis, and biodistribution, which may be a prerequisite for clinical applications.Keywords: micelles, blood components, phagocytosis, biodistribution